Fatal Systemic Morbillivirus Infection in Bottlenose Dolphin, Canary Islands, Spain - Eva Sierra (Emerging Infectious Diseases, 2014)
A systemic morbillivirus infection was diagnosed postmortem in a juvenile bottlenose dolphin stranded in the eastern North Atlantic Ocean in 2005. Sequence analysis of a conserved fragment of the morbillivirus phosphoprotein gene indicated that the virus is closely related to dolphin morbillivirus recently reported in striped dolphins in the Mediterranean Sea.